Analytical methods for energy diversity and security : portfolio optimization in the energy sector : a tribute to the work of Dr. Shimon Awerbuch - Awerbuch, Shimon; Bazilian, Morgan; Roques, Fabien A.; ScienceDirect eBooks (Amsterdam ; Boston ; London : Elsevier Science, 2008)
This is an ideal volume for professionals in academia, industry and government interested in the rapidly evolving area at the nexus between energy and climate change policy. The cutting-edge international contributions allow for a wide coverage of the topic. Energy Diversity and Security focuses on the consideration of financial risk in the energy sector. It describes how tools borrowed from financial economic theory, in particular mean-variance portfolio theory, can provide insights on the costs and benefits of diversity, and thus inform investment decision making in conditions of uncertainty. It gives the reader an in-depth understanding of how to manage risk at a time when the world's focus is on this area. The book provides insights from leading authorities in the area of energy security. It gives readers abundant, rigorous analysis and guidance at a critical time in facing the twin challenges of energy security and climate change. The book also highlights the role of clean energy technology in moving towards future diverse and intelligent electricity systems. It will be a trusted, first point of reference for decision-makers in the field of energy policy. The book includes a foreword by the 2007 Nobel Peace Prize winner. All royalties from sale of this book will be donated to charities working in the energy sector in the developing world. . Theoretical underpinning and applied use of Portfolio theory in the energy sector . In-depth consideration of risk . Contributions from leading international energy economists . Innovative methodologies for thinking about energy security and diversity.
Preface -- Foreword 1 / R. Pachauri, TERI -- Foreword 2 / Eddie O'Connor, Airtricity -- Reader's Guide / the editors -- Introduction: Analytic approaches to quantify and value fuel mMix diversity / the editors -- Part I: Assessing risks, costs and fuel mix diversity for electric utilities -- 1. Diversity and sustainable energy transitions: Multicriteria diversity analysis of electricity portfolios / by Andy Stirling -- 2. The value of renewable energy as a hedge against fuel price risk: Analytic contributions from economic and finance theory / by Mark Bolinger and Ryan Wiser -- 3. Using portfolio theory to value power generation investments / by the editors -- 4. Use of real options as a policy-analysis tool / by William Blyth -- Part II: Applying portfolio theory to identify optimal power generation portfolios -- 5. Efficient electricity generating portfolios for Europe: Maximizing energy security and climate change mitigation / by Shimon Awerbuch and Spencer Yang -- 6. Portfolio analysis of the future Dutch generating mix / by Jaap C. Jansen and Luuk Beurskens -- 7. The role of wind generation in enhancing Scotland's energy diversity and security: A mean-variance portfolio optimization of Scotland's generating mix / by Shimon Awerbuch, in collaboration with Jaap C. Jansen and Luuk Beurskens -- 8. Generation portfolio analysis for a carbon constrained and uncertain future / by Ronan Doherty, Hugh Outhred and Mark O'Malley -- 9. The economics of renewable resource credits / by Christiaan Hogendorn and Paul Kleindorfer -- Part III: Frontier applications of the mean-variance optimization model for electric utilities planning -- 10. Efficient and secure power for the United States and Switzerland / by Boris Krey and Peter Zweifel -- 11. Portfolio optimiztion and utilities' investments in liberalized power markets / by Fabien A. Roques, David M. Newbery, William J. Nuttall -- 12. Risk management in a competitive electricity market / by Min Liu and Felix F. Wu -- 13. Application of mean-variance analysis to locational value of generation assets / by Serhiy Kotsan and Stratford Douglas -- 14. Risk, embodied technical change and irreversible investment decisions in UK electricity production: An optimum technology portfolio approach / by Adriaan van Zon and Sabine Fuss -- Index -- Shimon Awerbuch biography -- Charity -- About the editors.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Electric power systems -- Management; Electric power production; Electric utilities -- Risk management; TECHNOLOGY & ENGINEERING -- Power Resources -- Electrical; Electric power production; Electric power systems -- Management; Electronic books